Teachers' attitudes towards students with disabilities: the role of the type of information provided in the students' profiles of children with disabilities. Issue 3 (4th May 2022) - Ginevra, Maria Cristina; Di Maggio, Ilaria; Valbusa, Isabella; Santilli, Sara; Nota, Laura
ABSTRACT: Teachers' attitudes towards students with disabilities have a crucial role in the effective implementation of the school inclusion process. This study examined the relationship of relevant teachers' personal variables (gender, age, length of professional experience, and the grade of the school in which they teach), characteristics of the students with disabilities (type of disability, gender), and contextual factors (type of information provided in the students' profiles of children with disabilities) with teachers' attitudes towards students with disabilities. A sample of 336 mainstream Italian primary and secondary teachers was involved. Results showed that teachers' gender, age, and length of professional experience were not related to their attitudes. Secondary school teachers hold more negative attitudes related to the social acceptability of students with disabilities. More negative attitudes related to school performance towards boys and students with intellectual disability, and more negative attitudes related to social acceptability towards students with behaviour problems were found. Lastly, the type of information provided in the students' profiles of children with disabilities positively impacted teachers' attitudes towards the students when the descriptions focused on their strengths. Implications of the results are discussed in terms of promoting teachers' positive attitudes towards students with disabilities.